A rare case of right atrial perforation and pericardial tamponade following leakage of bone cement - Renlang Liu; Zhirong Wang; Zhiwei Zhang; Hong You; Qi Ai; Wancun Jin; Qin Wu (Journal of Cardiothoracic Surgery)
Abstract Background Percutaneous vertebroplasty is commonly used to treats vertebral fractures, tumors, and osteolytic vertebral metastases. However, cement leakage during the procedure can lead to severe complications, including cardiac perforation. This report presents a case of right atrial perforation and pulmonary embolism caused by cement leakage, emphasizing the clinical significance of these events and discussing the treatment strategy. Case presentation A 57-year-old female was admitted to the hospital with a slipped lumbar vertebra and back pain, for which she underwent percutaneous vertebroplasty. On the 10th postoperative day, the patient suddenly developed chest tightness and shortness of breath, accompanied by a gradual decline in hemoglobin levels. After several imaging studies, a diagnosis of right atrial perforation caused by bone cement was confirmed. The patient subsequently underwent open cardiac foreign body removal and made a full recovery, with no residual cardiac dysfunction. Conclusion This case highlights the rare but serious complication of right atrial perforation caused by bone cement leakage during percutaneous vertebroplasty. The report emphasizes the importance of early identification of bone cement-related complications. While conservative management may suffice for pulmonary embolism, urgent surgical treatment is required for cardiac cement embolism to prevent further complications.